The Application of Learning Media Arabic Vocabulary Cards to Increase the Value of Speaking Skills in Arabic Language Class VIII A Featured MTsN 1 Jetis Ponorogo Academic Year 2021-2022 - Rahmanudin, Ii; Syauqi Saloom, Muhammad (Universitas Djuanda, 2024)
Madrasah Tsanawiyah 1 Ponorogo is particularly concerned with the discipline of Arabic language. Hence, all students are required to learn Arabic, starting from grade VII to grade IX, and Arabic teachers are required to use Arabic in teaching. And that students have not been able to answer questions during exams, actively speak Arabic, or speak when learning and in their daily lives because they only learn Arabic in the classroom. As a result, most teachers explain the lesson using Indonesian and other media that are less than the maximum for class learning. The purpose of this study is divided into two parts: 1) describing how students are active by using Arabic vocabulary cards as learning media to improve speaking skills. 2) Explain the benefit of using Arabic vocabulary cards in Arabic lessons to improve Grade VIII. Students at MTsN 1 Jetis Ponorogo. This type of research is approached as classroom action research (PTK). By conducting this research, the researchers will use the previous test method to get the data needed through observation and documentation. The results of this study are as follows: 1) The application of learning through the use of Arabic Vocabulary Card Learning Media with the Almasyah theory states that using this card improves student grades. 2) That the application of the Vocabulary Card Learning Media has reached the level desired by the researcher in Arabic Material Class VIII A MTsN 1 Jetis Ponorogo.